Die Dinge und ihre Verwandten. Zur Entwicklung von Sammlungen - Nicolaysen, Rainer (Hamburger Universitätsreden Neue Folge, 2017)
In the last few years scientific collections has gained significance. In particular, the "Recommendations on Scientific Collections as Research Infrastructures" published by the German Wissenschaftrat (Science Council) in January 2011 have caused a surge in attention.This volume of the series Hamburg's University Speeches (Hamburger Universitätsreden) documents the frame of the Annual Conference of the Society for University Collections (Gesellschafts für Universitätssammlungen) in 2016 and the lecture given by Ulrich Raulff, Director of the German Literary Archives in Marbach. In his text "The Things and their Relatives" he shows how an object without context immediately loses its meaning. Raulff ends his reflections on things and their collection with an appeal to the representatives of the scientific collections to conduct their own research, namely in their own collections. Archives, museums and collections should not wait for being researched. They should not limit themselves to the classical "research in indexing", but should initiate and carry out research projects themselves. Only through their own understanding of research a meaningful collection policy can be developed, which will really reach the present and the future. The text of the speech is followed by 30 colour photographs of special objects presented by Ulrich Raulff during his lecture in the atrium of the Hamburg State and University Library.